Figurative Language In The Poems Of Jalaluddin Rumi : A Sociolinguistic Perspective - Nuraeni, Anis; Dr. Maryadi, Dr. Maryadi M.A (2017)
This research has two major objectives proposed by the researcher, namely (1) to identify the types of figurative language used in the poetries by Jalaluddin Rumi and (2) to explain the meanings of figurative language used in the poems of Jalaluddin Rumi. The type of this research is descriptive qualitative. The data source of this research is taken from the poetries by Jalaluddin Rumi. Techniques of collecting data used are observation and documentation. The data was analyzed by using Leech's theory to identify the types of figurative language and Hymes' theory to explain the meaning of figurative language. The result shows that (1) the types of figurative language there are 13.51% of personification, 18.92% of hyperbola, 43.24% of metaphor, 18.92% of simile and 5.41% of litotes. The majority of figurative language types used in poetries by Jalaluddin Rumi is metaphor which has 16 out of 37 (43.24%). Meanwhile, (2) the meanings of figurative language there are 56.76% of suggestion meaning, 10.81% of command meaning and 32.43% of prohibitation meaning. The majority of figurative language meanings used in poetries by Jalaluddin Rumi is suggestion which has 21 out of 37 (56.76%).Keyworsds: gurativelanguage, poetries, Jalaluddin Rumi, types.